Expression of an scFv antibody fragment in Nicotiana benthamiana and in vitro assessment of its neutralizing potential against the snake venom metalloproteinase BaP1 from Bothrops asper - Gomes, Marinna (2019)
Human accidents with venomous snakes represent an overwhelming public health problem, mainly in rural populations of underdeveloped countries. Their high incidence and the severity of the accidents result in 81,000 to 138,000 deaths per year. The treatment is based on the administration of purified antibodies, produced by hyper immunization of animals to generate immunoglobulins (Igs), and then obtained by fractionating hyper immune plasma. The use of recombinant antibodies is an alternative to conventional treatment of snakebite envenoming, particularly the Fv fragment, named the single-chain variable fragment (scFv). We have produced recombinant single chain variable fragment scFv against the venom of the pit viper Bothrops asper at high levels expressed transiently and stably in transgenic plants and in vitro cultures that is reactive to BaP1 (a metalloproteinase from B. asper venom). The yield from stably transformed plants was significantly (p > 0.05) higher than the results in from transient expression. In addition, scFvBaP1 yields from systems derived from stable transformation were: transgenic callus 62 μg/g (±2); biomass from cell suspension cultures 83 μg/g (±0.2); culture medium from suspensions 71.75 mg/L (±6.18). The activity of scFvBaP1 was confirmed by binding and neutralization of the fibrin degradation induced by BnP1 toxins from B. neuwiedi and by Atroxlysin Ia from B. atrox venoms. In the present work, we demonstrated the potential use of plant cells to produce scFvBaP1 to be used in the future as a biotechnological alternative to horse immunization protocols to produce anti-venoms to be used in human therapy against snakebites.